Evaluation of Proinflamation Interleukin IL-6 in Thyroid Disorders Patients in Najaf Province - Naser, Naser Adris Naser; Mahmood, Thikra Abdullah (Medical Science Journal for Advance Research, 2024)
Background: Problems with the thyroid disorders can be caused by iodine deficiency or autoimmune diseases. Autoimmune thyroid disorders (AITD) are caused by an instability of the immune system that leads to an immune attack on the thyroid gland such as Graves' disease or Hashimoto's disease. Specific autoimmune diseases that affect a specific thyroid gland are known as AITDs. The study aims to identify the effect of interleukins (IL-6) on patients with thyroid disease. Methods: The current study includes more than 400 total samples, of which 140 samples underwent immunodiagnostics’ and were divided into 70 control groups: 35 Graves' illness and 35 Hashimoto's illness patients who visited Sadr Medical City (Diabetes and Endocrinology) and the specialty of Al-Zahraa Laboratory and some laboratories in Najaf Governorate from July 2023 to October 2023, ages 18–70. Concentrations of thyroid hormones T3, T4, and TSH were measured to identify patients with hypothyroidism or hyperthyroidism and compared to a control group. Results: It has found that patients with hypothyroidism enjoyed significantly lower intensities of T3, T4, as well as TSH, while their TSH degree increased significantly compared to the rest of the patients and the control group. Most of the patient samples were from hypothyroid patients. After that, special tests were performed to detect the presence of specific antibodies associated with this disease (AITD), namely ATPO and ATG, in addition to the clinical diagnosis of patients by the doctor. Secondly ATG was significantly increased in patients with Hashimoto's compared with patients with Graves' and fit controls, and ATPO concentration was significantly elevated in both patients with GD and HD compared with healthy controls. This study showed a higher incidence of AITD in females, as it was in Graves (84.8%) and Hashimoto's (77.1%), and the age group 30–50 years was more frequent in Graves (51.5%) and Hashimoto's (62.9%). smoking in the hypothyroid 29 (78.6%) and 27 (81.8%) patients, while in the non-smoking patients, the control was 8 (21.6%) hypothyroid and 6 (19.4%). There was a significant difference in the frequency distribution according to smoking among study groups (p = 0.0.03). Mental status was significant (p-value ≤ 0.05 was 0.00001). TSH, T3, T4, antTPO, and antTG are binding with Hashimoto's and Graves'. In immunological studies, the degree of IL-6 in serum is significantly higher in thyroid disorders (Hashimoto's disease was 9.665 and Graves' disease was 9.636) in the p-value ≤ 0.05 compared with the healthy group (mean =9.192), Comparative analysis shows the mean difference in concentration level of IL6 among patients with thyroid disorders. There's an important variation in the mean concentration of IL6 among patients with thyroid groups (Hashimoto's disease was 5.513 and Graves' disease was 5.541), though the concentration mean of the control group was 8.111. Conclusion: Anti TOP and AntiTG have a strong effect on interleukin-IL-6. Compared to the control group, individuals with hyperthyroidism and hypothyroidism had significantly lower IL6 levels. Pro-inflammatory cytokines, such as IL6 and others, have a positive correlation with psychopathology through various mechanisms impacting neurodevelopment, transmission, and synaptic plasticity; these differences are significantly different from those between thyroid disorders and mental status. Females are more likely to suffer from thyroid disorders than males are because of the "double effect" that women produce. The frequency distributions of the research groups differed significantly with respect to smoking.